The Dilemma Between Religious Doctrine and Political Pragmatism: Study of Hamas in Palestine - Mulawarman Hannase (Religió: Jurnal Studi Agama-agama, 2020)
This paper aims to examine how Hamas as an Islamic movement which adheres to the Muslim Brotherhood ideology came into the political public sphere from 2006 until today. Can Hamas maintain the purity of its religious doctrine when the movement engages in a political election in Palestine? This research uses a qualitative method and adopts the theory of political normalization by Antony Bubalo and Greg Feely to analyze how Islamists movement runs into a secular democratic system by participating in the election, establishing political parties, and contributing within a parliamentary and presidential system. From a theological perspective, this research shows that violence involved by an Islamist group in particular due to their theological interpretation. Meanwhile, from a political perspective, Hamas tries to adapt its approach with the political condition and runs with the contextual realm as well as other political groups from different ideological backgrounds.